Analysis of the Share Price of IDX Sharia Growth 30 Companies Listed on the Indonesia Stock Exchange - Ferdius Mooy, Welem; Purwanto, Setiyo (Journal of Accounting and Finance Management, 2024)
This study aims to analyze the effect of Net Profit Margin, Return on Asset and Earning Per Share on the stock price of Idx Sharia Growth 30 companies listed on the Indonesia Stock Exchange (IDX). The approach in this study is to use a quantitative approach and based on its objectives, this type of research is causal, namely research that explains the influence of an independent variable on bound variables. The population of this study is 30 Idx Sharia Growth 30 companies listed on the Indonesia Stock Exchange (IDX) in 2020-2023. The procedure for determining samples using the purposive sampling method is a sampling method that uses certain considerations. Based on the results of the selection, all companies meet the criteria. The independent variables in this study are Net Profit Margin, Return on Asset and Earning Per Share and the dependent variable is the stock price. Data analysis uses multiple linear regression analysis. The results of the analysis show that Net Profit Margin, Return on Asset and Earning Per Share have a positive and significant effect on stock prices. The results of the Coefficient of Determination showed that the Adjusted R-squared value was 63.2% and the remaining 36.8% was influenced by other factors that were not present in this study.